CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Eqaution of the tangent to $$x^{2}+y^{2}-6x+4y-12=0$$ at $$(-1, 1)$$


A
4x3y+7=0
loader
B
4x+3y7=0
loader
C
3x4y+2=0
loader
D
x2y+4=0
loader

Solution

The correct option is A $$4x-3y + 7 = 0$$

Equation of tangent to $$x^{2}+y^{2}-6x+6y-12=0$$ at (1,1) is $$T=0$$

$$xx_{1}+yy_{1}-3(x+x_{1})+2(y+y_{1})-12=0$$

$$-x+y-3x+3+2y+2-12=0$$

$$y-3y-4x-7=0$$

$$\Rightarrow 4x+7=3y$$


Maths

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image